Clinical characteristics and etiologies of bronchiectasis in Korean children: A multicenter retrospective study. (April 2019) - Lee, Eun; Shim, Jung Yeon; Kim, Hyung Young; Suh, Dong In; Choi, Yun Jung; Han, Man Young; Baek, Kyung Suk; Kwon, Ji-Won; Cho, Joongbum; Jung, Minyoung; Kim, Young Suh; Sol, In Suk; et al.
Abstract: Background: Bronchiectasis is a chronic pulmonary disease characterized by progressive and irreversible bronchial dilatation. The aim of the present study was to investigate the etiologies and clinical features of bronchiectasis in Korean children. Methods: We performed a retrospective review of the medical records for children diagnosed with bronchiectasis between 2000 and 2017 at 28 secondary or tertiary hospitals in South Korea. Results: A total of 387 cases were enrolled. The mean age at diagnosis was 9.2 ± 5.1 years and 53.5% of the patients were boys. The most common underlying cause of bronchiectasis was preexisting respiratory infection (55.3%), post-infectious bronchiolitis obliterans (14.3%), pulmonary tuberculosis (12.3%), and heart diseases (5.6%). Common initial presenting symptoms included chronic cough (68.0%), recurrent pneumonia (36.4%), fever (31.1%), and dyspnea (19.7%). The most predominantly involved lesions were left lower lobe (53.9%), right lower lobe (47.1%) and right middle lobe (40.2%). No significant difference was observed in the distribution of these involved lesions by etiology. The forced expiratory volume in 1 s (FEV1 ) levels were lowest in cases with interstitial lung disease-associated bronchiectasis, followed by those with recurrent aspiration and primary immunodeficiency. Conclusions: Bronchiectasis should be strongly considered in children with chronic cough and recurrent pneumonia. Long-term follow-up studies on pediatric bronchiectasis are needed to further clarify the prognosis and reduce the disease burden in these patients. Highlights: The bronchiectasis is common in respiratory infection and bronchiolitis obliterans. Common initial symptom in children with bronchiectasis is chronic cough. Pulmonary function is lowest in interstitial lung disease-associated bronchiectasis.